Genome-wide association analyses identify 44 risk variants and refine the genetic architecture of major depression - Ripke, Stephan; Trzaskowski, Maciej; Byrne, Enda M.; Adams, Mark J.; Andlauer, Till M. F.; Bacanu, Silviu-Alin; Beekman, Aartjan F. T.; Bigdeli, Tim B.; Binder, Elisabeth B.; Blackwood, Douglas R. H.; Bybjerg-Grauholm, Jonas; Castelao, Enrique; et al. (Nature genetics, 2018)
Major depressive disorder (MDD) is a common illness accompanied by considerable morbidity, mortality, costs, and heightened risk of suicide. We conducted a genome-wide association meta-analysis based in 135,458 cases and 344,901 controls and identified 44 independent and significant loci. The genetic findings were associated with clinical features of major depression and implicated brain regions exhibiting anatomical differences in cases. Targets of antidepressant medications and genes involved in gene splicing were enriched for smaller association signal. We found important relationships of genetic risk for major depression with educational attainment, body mass, and schizophrenia: lower educational attainment and higher body mass were putatively causal, whereas major depression and schizophrenia reflected a partly shared biological etiology. All humans carry lesser or greater numbers of genetic risk factors for major depression. These findings help refine the basis of major depression and imply that a continuous measure of risk underlies the clinical phenotype. A genome-wide association meta-analysis of individuals with clinically assessed or self-reported depression identifies 44 independent risk loci. Comparisons with other psychiatric disorders and candidate gene analyses provide new insights into major depressive disorder.